Menyoal Hukum Nikah Misyar dalam Potensinya Mewujudkan Maqasid al-Asliyyah dan al-Tab'iyyah dalam Perkawinan Umat Islam - Busyro Busyro (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
The main purpose of marriage is having progeny besides for having happy and restful life. It is common saying that every people that get married are having kids besides other purposes in their lives. Unlike the purpose of common marriage, the main purpose of nikah misya>ris not for having kids. Yet, nikah misya>r is the marriage that aims only to have life together legally and to get sexual pleasure. This kind of marriage is done like common marriage in Islamic law that still fulfils the requirements and the principles of marriage. Some of Ulamas see that nikah misya>r is allowed to do. They argue that the purpose of marriage is not only for having descendant, but also for enjoyment and happiness. Ignoring to have kids in marriage aim actually is not a digression of Islamic rules. Otherwise, some of Ulama strongly forbid this kind of marriage because it does not actualize the interest of marriage that is to have posterity. However, in maqa>ṣid al-aṣliyyah (primary purpose of syari’ah) and maqa>ṣid al-tab’iyyah (secondary purpose of syari’ah) view, nikah misya>r should be banned because it clearly infringes the will of The Lawmaker, al-Syâri’ (Allah).